RANCANG BANGUN ALAT PENANAM BENIH KEDELAI (Glycine max L.) (Design and Construction of Soybean Grains Seeder (Glycine max L.)) - Ari Budiarto Bancin; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Quick Drop System soybean seeder models  still using human power as a source of propulsion. The purpose of this research was to design, build, and test a soybean seeder to be more effective. This research was conducted from August to October 2016 at the Laboratory Agriculture Engineering, Faculty of Agriculture, Universitas Sumatera Utara. Models of this research are literature studies, designing forms, manufacture/coupling components, testing equipment and observation parameters. The parameters observed were effective capacity, consistency of the distribution of the seeds along the length of the row, fuel consumption, effectiveness equipment and consistency of sowing depth uniformity. Based on this research, it was summarized that the effective capacity of the equipment was 0,073 ha/hour and 2,511 ha/L for diesel fuel. Keywords : Soybean, seeder, effectiveness. ABSTRAK Model alat penanam kedelai Quick Drop System masih menggunakan tenaga manusia sebagai sumber tenaga penggerak. Penelitian ini adalah penelitian mengenai mendesain, membuat dan menguji alat penanam kedelai yang lebih efektif. Penelitian ini dilaksanakan pada bulan Maret hingga Agustus 2016 di Laboratorium Keteknikan Pertanian Fakultas Pertanian Universitas Sumatera Utara, dengan cara studi literatur, perancangan bentuk, pembuatan/perangkaian komponen-komponen, pengujian alat dan pengamatan parameter. Parameter yang diamati adalah kapasitas efektif alat, konsistensi jarak tanam, konsumsi bahan bakar, efektivitas alat, dan konsistensi jumlah biji yang ditanam. Hasil penelitian menunjukkkan bahwa kapasistas efektif alat adalah 0,073 ha/jam. Bahan bakar yang digunakan adalah 2,511 ha/L solar. Kata Kunci : Kedelai, alat penanam, efektivitas.